THE ROLE OF HEALTH MANAGEMENT IN IMPROVING THE QUALITY OF MEDICAL SERVICES - Frandy Putra Perdamen Tarigan; Juniarto Dwi Utomo; Krisna Meidiyantoro Baharuddin; Kasmin Kasmin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Health management plays a crucial role in improving the quality of medical services in the modern era, where the complexity and demands on health services are increasing. Through efficient resource management, developing the competence of medical personnel, and implementing a strict patient safety system, health management can ensure that the services provided meet high standards and patient expectations. Systematic performance evaluations and the use of advanced information technology, such as electronic medical records, strengthen the effectiveness of evidence-based decision making. Collaboration between health professions and patient involvement in the care process are also important elements in improving service quality. In addition, health management plays a role in increasing service accessibility, especially for underserved communities. With an evidence-based approach and continuous innovation, health management can meet future challenges and contribute to a more responsive and quality health system. Through these efforts, it is hoped that the quality of medical services can continue to be improved, leading to better public health outcomes.